TPR: The Old but Gold Strategy in Enlarging Young Learners’ Vocabulary - Ahmad Zainudin (Jurnal Bahasa dan Sastra, 2018)
Abstract: English has a decisive role in the global era and is required by all students to master and acquire. This paper aimed at reviewing literature to help teachers enlarge young English learners’ vocabulary. The problem is that they are afraid to say words because they are in lack number of vocabularies related to what level they should use. EFL school students would need an active vocabulary at least 3000 high-frequency words of English. This would be great for students to develop the knowledge of vocabulary, or it can be encouraged for them to have an average of seven words per day. Therefore, this paper focused on discussing Total Physical Response (TPR) which concerns on speech and actions at the same time. It could be an old strategy but still the gold one which emphasizes meaningful and purposeful vocabulary for young learners. Keywords: vocabulary, young learners, TPR Abstrak: Bahasa Inggris mempunyai sebagai peran penting yang menentukan dalam era global dan semua pelajar dituntut untuk menguasainya. Artikel ini bertujuan meninjau literatur untuk memperluas kosakata pelajar, terutama pelajar muda. Masalahnya adalah mereka takut untuk mengucapkan kata dalam bahasa Inggris karena mereka kekurangan jumlah kosa kata yang berhubungan dengan tingkat apa yang harus mereka lakukan. Pelajar sekolah EFL (English as a Foreign Language) membutuhkan kosakata aktif setidaknya 3000 kata bahasa Inggris. Jumlah ini bagus bagi siswa untuk mengembangkan pengetahuan kosa kata, atau dapat disoroti untuk rata-rata tujuh kata per hari. Oleh karena itu, artikel ini berfokus pada membahasa tentang Total Physical Response (TPR) yang strategi pembelajaran kosa kata bahasa Inggris dimana berbicara dan melakukan tindakan pada saat yang sama. Ini dapat saja dianggap sebagai strategi lama tetapi tetap merupakan strategi emas yang menekankan penguasaan kosakata yang penuh makna dan tujuan bagi pembelajar muda. Kata-kata kunci: kosa kata, pembelajar muda, TP